IMPACT OF BANK’S CORPORATE SOCIAL RESPONSIBILITIES ON CUSTOMER BUYING ATTITUDE: THE CASE OF GHANAIAN UNIVERSAL BANKS - Ayam, A. J. R.; Dorsaa, F. K.; Anderson, E.; Mensah, S. (UDS International Journal of Development, 2022)
Universal banks in Ghana have witnessed stiff competition and declining customer growth in recent times. These banks have sort to adopt Corporate Social Responsibility (CSR) activities as a means to attract and build customer confidence and loyalty. The study employed quantitative research methodology with a 5 point Likert-Scale well validated research instrument. This correlational study seeks to measures the relationship between the CSR factors and Banks customer buying attitude. The results of the study revealed that there was a statistically medium to small relationship between the CSR factors and banks customer buying attitude. The study recommendations should assist universal banks in Ghana to tailor their CSR activities to achieve optimum customer confidence and loyalty. Keywords: Corporate Social Responsibility, Corporate Social Responsibility Factors, Customer Buying Attitude, Banks, Ghana Universal Banks.